Reduced Function and Diversity of T Cell Repertoire and Distinct Clinical Course in Patients With IL7RA Mutation - Lev, Atar; Simon, Amos J.; Barel, Ortal; Eyal, Eran; Glick-Saar, Efrat; Nayshool, Omri; Birk, Ohad; Stauber, Tali; Hochberg, Amit; Broides, Arnon; Almashanu, Shlomo; Hendel, Ayal; et al. (Frontiers in Immunology, 2019)
The alpha subunit of IL-7 receptor (IL7R7) is critical for the differentiation of T cells, specifically for the development and maintenance of γT cells. Mutations in IL7RA are associated with Severe Combined Immunodeficiency (SCID). Infants with IL7 RA deficiency can be identified through newborn screening program. We aimed at defining the immunological and genetic parameters that are directly affected by the IL7RA mutation on the immune system of five unrelated patients which were identified by our newborn screening program for SCID. The patients were found to have a novel identical homozygote mutation in IL7RA (c.120 C>G; p.F40L). Both surface expression of IL7Rα and functionality of IL-7 signaling were impaired in patients compared to controls. Structural modeling demonstrated instability of the protein structure due to the mutation. Lastly the TRG immune repertoire of the patients showed reduced diversity, increased clonality and differential CDR3 characteristics. Interestingly, the patients displayed significant different clinical outcome with two displaying severe clinical picture of immunodeficiency and three had spontaneous recovery. Our data supports that the presented IL7RA mutation affects the IL-7 signaling and shaping of the TRG repertoire, reinforcing the role of IL7RA in the immune system, while non-genetic factors may exist that attribute to the ultimate clinical presentation and disease progression.